Application of carrageenan–PVA bioplastic reinforced with ionic gelation-derived nanochitosan as sustainable packaging for fishballs: Aplikasi bioplastik karagenan–PVA berpenguat nanokitosan hasil gelasi ionik sebagai kemasan berkelanjutan untuk produk bakso - Fadhallah, Esa Ghanim; Febriati, Nurullia; Rahmawati, Rahmawati (Jurnal Pengolahan Hasil Perikanan Indonesia, 2026)
Shrimp shell waste generated by seafood processing industries remains underutilized and may contribute to environmental pollution. Valorization of this waste as a source of nanochitosan for carrageenan–polyvinyl alcohol (PVA)-based bioplastic films represents a promising approach for sustainable food packaging development. This study aimed to synthesize and characterize carrageenan–PVA bioplastic films incorporated with nanochitosan prepared via ionic gelation and evaluate their potential as packaging materials for fishballs during storage. The study employed a randomized block design with five nanochitosan concentrations (0, 0.5, 1.0, 1.5, and 2.0%) and three replicates. The evaluated parameters included mechanical properties, water vapor transmission rate (WVTR), swelling behavior, biodegradability, and application tests on fish balls. The synthesized nanochitosan exhibited an average particle size of 162.3±36.8 nm with a polydispersity index of 0.489. The incorporation of nanochitosan significantly increased the tensile strength and elongation while reducing the WVTR and swelling values. However, the film thickness and Young’s modulus were not significantly affected. The bioplastic films exhibited tensile strengths of 20.40–24.94 MPa, elongations of 448.75–583.75%, and thicknesses ranging from 0.09 to 0.17 mm. The best performance was obtained at 2.0% nanochitosan incorporation, resulting in the lowest WVTR value of 1.34 g/m²/day. Soil burial tests revealed that the bioplastic films completely degraded within 3–6 d. The application of the films as packaging showed potential to preserve the quality of fishballs by reducing weight loss and maintaining the moisture content, texture, and protein content during 14 days of storage at 4°C. These findings indicate that the developed bioplastic films have strong potential as environmentally friendly packaging materials for fishery products.